Growth and Production of Leaves Thalassia hemprichii on The Suli Coastal Waters, Ambon Island - Charlotha Irenny Tupan; Prulley Anette Uneputty (Institut Teknologi Sepuluh Nopember, 2018)
The aims of this study were to analyze the growth rate, production and biomass of Thalassia hemprichii leaves on different substrates in Suli coastal waters, Ambon Island. Data were collected at muddy substrate and sandy substrate by using tagging method. Tagging was applied weekly to 30 seagrass shoots for one month on each station. The growth rate of Thalassia hemprichii leaves ranged from 0.27±0.45 to 0.46±0.53 cmday-1. Production ranged from 5.08 to 8.64 gADWm-2day-1 and the biomass ranged from 245 to 541 gADWm-2.. The growth and production of T. hemprichii leaves is higher in sandy substrates than in muddy substrates